Great Lakes at Ten Miles an Hour. - Shevory, Thomas (University of Minnesota Press, 2017)
The Great Lakes are a remarkable repository of millions of years of complex geological transformations and of a considerably shorter, crowded span of human history. Over the course of four summers, Thomas Shevory rode a bicycle along their shores, taking in the stories the lakes tell--of nature's grandeur and decay, of economic might and squandered promise, of exploration, colonization, migration, and military adventure. This book is Shevory's account of his travels, shored up by his exploration of the geological, environmental, historical, and cultural riches harbored by North America's great inland seas. For Shevory, and his readers, his ride is an enlightening, unfailingly engaging course in the Great Lakes' place in geological time and the nation's history. Along the northern shore of Lake Huron, one encounters the scrubbed surfaces of the Canadian Shield, the oldest exposed rock in North America. Growing out of the crags of the Niagara Escarpment, which stretches from the western reaches of Lake Michigan to the spectacular waterfalls between Erie and Ontario, are the white cedars that are among the oldest trees east of the Mississippi. The lakes offer reminders of the fur trade that drew voyageurs to the interior, the disruption of Native American cultures, major battles of the War of 1812, the shipping and logging industries that built the Midwest, the natural splendors preserved and exploited, and the urban communities buoyed or buried by economic changes over time. Throughout The Great Lakes at Ten Miles an Hour, Shevory describes the engaging characters he encounters along the way and the surprising range of country and city landscapes, bustling and serene locales that he experiences, making us true companions on his ride.